Nurses’ Informatics Competency Assessment, Perceived Usability, And Implementation Of Electronic Health Records In A Tertiary Hospital In Quezon City, Philippines - B. Yngente, Catherine Eve; Aliswag DNS, Emerson G. (Journal of Neonatal Surgery, 2025)
Background: Electronic Health Records (EHRs) have been available for the past few decades; however, the geographical disparity in their procurement and utilization varies greatly across countries, based on their healthcare financing schemes, which are significantly influenced by national budget allocations for health and the level of capitalism. The Philippines, a developing country, houses some of the leading healthcare institutions in Southeast Asia. One of which, the research locale of this study, has just recently acquired its EHR and is undergoing a transition towards its full utility. Aligned with this transition is the need to ensure that nurses, as one of the primary end-users of this newly acquired technology, are proficient in its use. It is based on the increasing necessity for digitizing healthcare in the Philippines, particularly with the move towards universal healthcare and the necessity for effective, technology-based patient management. Hence, arriving at the main objective of this study, which is to examine the role of nurses' informatics competence and perceived ease of use of Electronic Health Records (EHRs) in successful implementation in healthcare environments. The selected hospital location is a model of best practices for the utilization of EHRs, providing an appropriate setting for consideration of how technology tools affect the quality of care. The research highlights three interconnected areas: nurses’ informatics competency, the perceived usability of EHR systems, and the effectiveness of EHR implementation on patient care outcomes. Competency in informatics ensures accurate documentation and data use, while usability influences whether nurses can efficiently and confidently navigate EHRs. Successful implementation relies not only on technology itself but also on training, infrastructure, and organizational support. Ultimately, the study highlights the need to enhance nurses' skills, improve system usability, and facilitate implementation for maximizing patient outcomes and maintaining digital healthcare transformation. Methods: In this study, the researcher used a quantitative approach to understand how nurses' informatics skills and their experience using Electronic Health Records (EHRs) impact patient care. To do this, they used correlation methods (like Pearson’s r, Spearman’s rho, and Kendall’s Tau-B) to explore how strongly these factors are connected. They also applied regression analysis to see if better informatics skills and perceived EHR usability could predict better patient outcomes. Finally, a mediation analysis helped show that when nurses find EHR systems easier to use, their informatics skills have an even stronger effect on the quality of care, making usability an important link between skill and performance. Result: This study explored how nurses’ informatics competency and the perceived usability of Electronic Health Records (EHRs) jointly influence patient healthcare outcomes. Results across correlation, regression, and mediation analyses consistently showed that both factors significantly and positively affect care effectiveness. Informatics competency was strongly correlated with better outcomes (r = 0.682), while EHR usability showed an even stronger relationship (r = 0.787). Regression analysis revealed that informatics skills explained 46.6% of outcome variance, and usability explained 62%. Mediation analysis confirmed that perceived usability serves as a key bridge between competency and performance, with a stronger indirect effect (β = 0.429) than the direct one (β = 0.253). Overall, the study emphasizes that improving both nurses’ digital skills and the usability of EHR systems is essential for enhancing patient outcomes. Conclusion: This study concludes that both nurses’ informatics competency and the perceived usability of Electronic Health Records (EHRs) significantly improve patient healthcare outcomes. Informatics skills enhance how nurses perceive EHR systems, which in turn leads to better clinical performance and care quality. The mediation analysis highlights usability as a crucial link between technical skills and patient outcomes. Therefore, improving both informatics training and EHR design is essential for delivering safer, more efficient, and patient-centered care